1999
DOI: 10.1016/s0014-5793(99)00424-x
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial expression of cellular protooncogene c‐ski and its regulation by estradiol‐17β

Abstract: The expression of the cellular protooncogene c-ski was examined in the rat uterus. In situ hybridization revealed that c-ski mRNA was expressed in the uterus of the adult rat on the day of estrous and localized mainly in the luminal and glandular epithelia. To test the possibility that the expression of c-ski mRNA is induced by estrogen, rats were ovariectomized and estradiol-17L L (E 2 ) was injected. The expression of c-ski mRNA was upregulated 3 h after E 2 treatment, reaching the highest level at 6 h and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…A thorough analysis of expression levels of c-Ski or c-SnoN in normal and cancerous breast tissue has not been reported, but the recent identification of their involvement in TGF-β signaling warrants closer investigation of this issue. Furthermore, a recent study suggested that c-Ski expression is upregulated in response to estrogen signaling in epithelial cells of the uterus [96], raising the possibility that c-Ski might also be involved in the interactions between estrogen and TGF-β in breast cancer.…”
Section: Altered Expression Of Tgf-beta/smad Inhibitory Moleculesmentioning
confidence: 99%
“…A thorough analysis of expression levels of c-Ski or c-SnoN in normal and cancerous breast tissue has not been reported, but the recent identification of their involvement in TGF-β signaling warrants closer investigation of this issue. Furthermore, a recent study suggested that c-Ski expression is upregulated in response to estrogen signaling in epithelial cells of the uterus [96], raising the possibility that c-Ski might also be involved in the interactions between estrogen and TGF-β in breast cancer.…”
Section: Altered Expression Of Tgf-beta/smad Inhibitory Moleculesmentioning
confidence: 99%
“…For example, Ski is expressed in proliferating myoblast [6] and uterine epithelial cells [7]. In the uterus, endometrial c-ski gene expression has been induced by estrogen treatment, which is known to induce proliferation of uterine epithelial cells [7], and progesterone treatment eliminated estrogeninduced c-ski expression [30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mice lacking c-ski show perinatal lethality due to defects in neurulation and craniofacial patterning as well as skeletal muscle development, and excessive apoptosis has been detected in c-skideficient mouse embryos [4,5], supporting the idea that Ski can act as an anti-apoptotic factor [6]. It has also been suggested that c-ski is involved in mediating the proliferative effect of 17β-estradiol in uterine epithelial cells [7]. Thus, c-ski gene product (Ski) has been implicated as having dual roles in both regulating proliferation and differentiation of cells.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Partial fragments of double-stranded cDNA encoding the rat c-ski gene (561 bp) and myogenin (517 bp) were produced by polymerase chain reaction (PCR) as previously described (Wright et al 1989;Yamanouchi et al 1999). The primer sets used for PCR were as follows: for c-ski, forward primer 5Ј-ACC ATC TCG TGC TTC GTG GTG GGA-3Ј and reverse primer 5Ј-CTC CTT GCC CGT GTA ATC CTG GCT-3Ј; for myogenin, forward primer 5Ј-AGC TCC CTC AAC CAG GAG GA-3Ј and reverse primer 5Ј-GGG CTC TCT GGA CTC CAT CT-3Ј.…”
Section: Probes For Hybridizationmentioning
confidence: 99%